Effects of royal jelly on biochemical and reproductive parameters in hyperandrogenised female rats - Hamid, Norhamidar Ab (2018)
Polycystic ovary syndrome (PCOS) is a common endocrine abnormality in women characterised by hyperandrogenism, ovulatory dysfunction and polycystic ovary. Royal jelly (RJ) is traditionally consumed for enhancement of female reproductive function and fertility. The aims of this study were to analyse the composition of RJ and to evaluate the effects of RJ on biochemical and reproductive parameters in hyperandrogenised female rats. Forty immature female rats (three weeks old, 40-50 g) were randomly divided into 5 groups i.e. Control, Testosterone (T), T+100RJ (100 mg/kg/day RJ), T+200RJ (200 mg/kg/day RJ) and T+400RJ (400 mg/kg/day RJ) groups. Hyperandrogenic state was induced by giving testosterone propionate (10 mg/kg) intraperitoneally for three weeks followed by RJ via oral gavage daily for four weeks. Vaginal smear was done daily for assessment of oestrus cycle. At the end of the study, all rats were sacrificed and blood was collected for reproductive hormones levels and oxidant-antioxidant status assessment. RJ contained nutrient and phytochemical compounds with beneficial biological activity including oestrogenic and antioxidant properties. Body weight gain and fasting blood glucose level showed no significance differences among all groups. The percentage of regular oestrus cycle was significantly lower in T group compared to control and T+200RJ groups. T and oestradiol (E2) levels were significantly higher while folliclestimulating hormone (FSH) was significantly lower in T group compared to control group. In T+200RJ group, FSH level was significantly higher while luteinizing hormone (LH), T and E2 levels were significantly lower compared to T group. Thehistological results showed the numbers of primary and cystic follicles were significantly higher while numbers of secondary follicle and corpora luteum were significantly lower in T group compared to control group. In addition, the numbers of primary and cystic follicles were significantly lower and numbers of secondary follicle and corpora luteum were significantly higher in T+200RJ compared to T, T+100RJ and T+400RJ groups but not significantly different from control group. Malondialdehyde (MDA) and glutathione peroxidase (GPx) activities were significantly higher while total antioxidant capacity (TAC) level was significantly lower in T group compared to control group. However, in T+200RJ group, MDA level and GPx activity were significantly lower while TAC level was significantly higher compared to T group. These findings might suggest that RJ at 200 mg/kg/day for 4 weeks improves reproductive hormone levels, oestrus cycle regularity, ovarian histology and ovarian oxidant-antioxidant status in hyperandrogenised immature rats as PCOS rat model. This effect could be attributed partly to the combined effects of its phytochemical compounds that have oestrogenic and antioxidant properties. In conclusion, RJ at the dose of 200 mg/kg/day significantly improves biochemical and reproductive changes in hyperandrogenised female rats which need further study to evaluate its exact mechanism of action.